2017
DOI: 10.22547/ber/9.2.4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supportive Work Environment, Trust, and Self-Efficacy on Organizational Learning and Its Effectiveness: A Stimulus-Organism Response Approach

Abstract: This study examines the relationship among management and peer support, trust, self-efficacy, organizational learning, and organizational effectiveness. Within organization, supportive work environment plays a significant role in the establishment of employees' learning process. The causal design is used to analyze the impact of supportive work environment on employees' psychological influence (i.e. trust and self-efficacy) and organizational learning. The nature of the study is cross-sectional with convenienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 94 publications
1
26
0
1
Order By: Relevance
“…The SOR framework has been used in organizational behavior studies to explain how work features affect employees' behaviors. For example, Attiq et al (2017) found that support from top management and co-workers (stimulus) had a significant positive impact on organizational learning and organizational effectiveness (responses) and that employees' trust and self-efficacy (organism) mediated the relationship between stimulus and response. Zhu et al (2012) used the SOR framework to link employee's perception of organizations' corporate social responsibility (stimulus) with their satisfaction (reflecting the internal status of the organism) and loyalty (response).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The SOR framework has been used in organizational behavior studies to explain how work features affect employees' behaviors. For example, Attiq et al (2017) found that support from top management and co-workers (stimulus) had a significant positive impact on organizational learning and organizational effectiveness (responses) and that employees' trust and self-efficacy (organism) mediated the relationship between stimulus and response. Zhu et al (2012) used the SOR framework to link employee's perception of organizations' corporate social responsibility (stimulus) with their satisfaction (reflecting the internal status of the organism) and loyalty (response).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Not properly filling the questionnaire and the lack of respondent support typically obscure the practice of collecting data in Pakistan (Taskeen et al, 2014). Accordingly, when gathering primary data in Pakistan, non-probability sampling techniques (such as convenience and purposive) is preferably used and assumed to be the most appropriate form of sampling (Attiq, Rasool & Iqbal, 2017). Consequently, this research used a purposive sample.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…As also mentioned earlier, it is a popular method of testing the indirect effect in the presence of multiple mediators (Shrout & Bolger, 2002). The bootstrapping procedures in SEM are widely used while performing sequential or serial mediation (Attiq et al, 2017). The advantage of using the bootstrapping approach is that it makes no assumption about the distribution of the standard error associated with the indirect effect and provides confidence intervals for the estimate.…”
Section: Hypotheses Testing -Mediation Analysismentioning
confidence: 99%
“…CLT postulates that if the cognitive capacity to process the information is overloaded, then the behavioral response (of the organism) can be adversely affected ( Sweller, 2011 ), contributing to the possibility of irrational action. An individual's previous knowledge, thinking skills, and self-efficacy have moderating effects on the behavioral response ( Attiq et al, 2017 ). Although the environment ultimately pushes organisms toward certain reactions, individual and group characteristics may act as an opposing or amplifying force.…”
Section: Introductionmentioning
confidence: 99%